Uruguay : Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2015)
Uruguay currently stands out in Latin America for its higher per capita income, low inequality, low poverty, and virtual absence of indigence. As a proportion of the total population, the size of Uruguays middle class is the largest in Latin America, encompassing well over half the population. The country ranks at or near the top of Latin America on many measures of well-being. The stability of its institutions and low levels of corruption are reflected in a high degree of trust in government by citizens. The countrys smallness and openness, and its strong and deeply rooted social compact – help explain Uruguays achievements in the areas of growth, poverty reduction and shared prosperity as well as future opportunities and challenges. The World Bank has two goals for Uruguay to sustain the social compact by strengthening inclusion and equality of opportunity and to sustain growth with productivity and competitiveness.